Discrete oligodimethylsiloxane–oligomethylene di- and triblock co-oligomers: synthesis, self-assembly and molecular organisation12. Issue 20 (2nd May 2018) - van Genabeek, Bas; de Waal, Bas F. M.; Palmans, Anja R. A.; Meijer, E. W.
Abstract : A new class of discrete-length block co-oligomers comprising oligodimethylsiloxane ( o DMS) and oligomethylene ( o M) is presented. Abstract : A new class of discrete-length block co-oligomers comprising oligodimethylsiloxane ( o DMS) and oligomethylene ( o M) is presented. For this, o M blocks containing up to 69 backbone carbons are synthesised via an iterative, Wittig reaction-based strategy. Ligation with o DMS hydrides permits the formation of a library of block co-oligomers (BCOs) in which the block configuration, MW, and composition can be tuned. Differential scanning calorimetry and small-angle X-ray scattering show that all BCOs exhibit microphase separation into well-ordered lamellar morphologies, driven by the crystallisation of the o M blocks. Pre-melting order–order transitions are present for a number of BCOs, resulting in an alteration of the o M crystal packing as well as in changes of the overall microphase-segregated structure. As a result of the discrete nature of the BCO chains, we propose models that describe the molecular organisation within the microphase-segregated structures by evaluating the changes in the lamellar thickness upon varying the BCO architecture.